Clinical characteristics and gene analysis of long QT syndrome in 15 children - Yiwei, Li; Peiwen, Gong; Tiewei, Lv; Huichao, Sun (Frontiers in Pediatrics, 2025)
ObjectiveTo elucidate the genetic and clinical characteristics of children diagnosed with long QT syndrome (LQTS) at our institution.Study designThis was a retrospective study. Clinical data and gene detection results of 15 cases diagnosed with congenital LQTS at our center from January 1, 2018 to December 30, 2023 were collected and analyzed using independent sample t-test and Levene's test for equality of variances.ResultsThe 15 LQTS cases included 7 females and 8 males. The mean age of onset for females (11.83 ± 3.48 years) was later than that for males (8.06 ± 2.50 years), and the mean QTc value for females (564.57 ± 20.72 ms) was higher than that for males (502. 25 ± 48.62 ms), both differences were statistically significant (P < 0.05). Intense exercise and psychological stress are the most common predisposing factors in these cases. Gene mutations were found in 14 of the 15 cases and most mutations (13/14) were inherited from parents. According to the mutation sites, the most common mutation type was missense mutations (11/15). One genetically exclusive case with a Schwartz score of 4 was clinically diagnosed with LQTS after excluding other diseases.ConclusionsIn this cohort, age of onset and QTc value are different between male and female. The most common primary symptom of LQTS is syncope. Most LQTS patients have a mutated gene inherited from their parents, and the most common pathogenic gene is KCNQ1.